Comunicación estratégica y su incidencia en los procesos administrativos de los empleados de la empresa agricolarisa del cantón Palenque - Macias Moreira, Mayber Maribel (2021)
The development of this research is aimed at identifying how strategic communication affects the administrative processes of the employees of the company "Agricolarisa" of the Palenque canton. This company is dedicated exclusively to the purchase and production of bananas, the sale of the production is transferred in box or in bulk, it maintains direct agreements with Veconsa, Samiya, Inalecsa and Life food product. The problems observed in this company are based on the deficient communication that they maintain within it, as well as the failure to comply with the stages of the administrative process. For the development of the research, the type of descriptive study was used in such a way that it allowed us to describe each of the most important characteristics of the problem, in addition, the technique that was used was the survey with a bank of 8 questions applied to the 6 company employees and oriented to collect relevant information for the analysis and interpretation of the most relevant findings. Based on those carried out in the research, it can be mentioned that communication in a company is one of the fundamental keys to believe its success and growth, the administrative management processes that are applied in the "Agricolarisa" company must improve in order to achieve the objectives that are set.